Guinea worm in domestic dogs in Chad: A description and analysis of surveillance data. - Sarah Anne J Guagliardo; Sharon L Roy; Ernesto Ruiz-Tiben; Hubert Zirimwabagabo; Mario Romero; Elisabeth Chop; Philippe Tchindebet Ouakou; Donald R Hopkins; Adam J Weiss (Public Library of Science (PLoS), 2020)
After a ten-year absence of reported Guinea worm disease in Chad, human cases were rediscovered in 2010, and canine cases were first recorded in 2012. In response, active surveillance for Guinea worm in both humans and animals was re-initiated in 2012. As of 2018, the Chad Guinea Worm Eradication Program (CGWEP) maintains an extensive surveillance system that operates in 1,895 villages, and collects information about worms, hosts (animals and humans), and animal owners. This report describes in detail the CGWEP surveillance system and explores epidemiological trends in canine Guinea worm cases during 2015-2018. Our results showed an increased in the number of canine cases detected by the system during the period of interest. The proportion of worms that were contained (i.e., water contamination was prevented) improved significantly over time, from 72.8% in 2015 to 85.7% in 2018 (Mantel-Haenszel chi-square = 253.3, P < 0.0001). Additionally, approximately 5% of owners of infected dogs reported that the dog had a Guinea worm-like infection earlier that year; 12.6% had a similar worm in a previous year. The proportion of dogs with a history of infection in a previous year increased over time (Mantel-Haenszel chi-square = 18.8, P < 0.0001). Canine cases were clustered in space and time: most infected dogs (80%) were from the Chari Baguirmi (38.1%) and Moyen Chari Regions (41.9%), and for each year the peak month of identified canine cases was June, with 78.5% occurring during March through August. Findings from this report evoke additional questions about why some dogs are repeatedly infected. Our results may help to target interventions and surveillance efforts in terms of space, time, and dogs susceptible to recurrent infection, with the ultimate goal of Guinea worm eradication.